Supplemental blue light increases growth and quality of greenhouse pak choi depending on cultivar and supplemental light intensity - Yin-jian ZHENG; Yi-ting ZHANG; Hou-cheng LIU; Ya-min LI; Ying-liang LIU; Yan-wei HAO; Bing-fu LEI (Journal of Integrative Agriculture, 2018)
To evaluate the supplementary blue light intensity on growth and health-promoting compounds in pak choi (Brassica campestris ssp. chinensis var. communis), four blue light intensity treatments (T0, T50, T100 and T150 indicate 0, 50, 100, and 150 µmol m−2 s−1, respectively) were applied 10 days before harvest under greenhouse conditions. Both of cultivars (greenand red-leaf pak choi) under T50 had the highest yield, content of chlorophyll and sugars. With light intensity increasing, antioxidant compounds (vitamin C and carotenoids) significantly increased, while nitrate content showed an opposite trend. The health-promoting compounds (phenolics, flavonoids, anthocyanins, and glucosinolates) were significantly higher under supplementary light treatment than T0, so as the antioxidant capacity (2,2-diphenyl-1-picrylhydrazyl and ferric-reducing antioxidant power). The species-specific differences in photosynthetic pigment and health-promoting compounds was found in green- and red-leaf pak choi. T50 treatment could be used for yield improvement, whereas T100 treatment could be applied for quality improvement. Results showed that blue light intensity can regulate the accumulation of biomass, morphology and health-promoting compounds in pak choi under greenhouse conditions.